(3GSJbdGdjI GdHfhc GdeQcRjI Hjf GdeaJQV hGdhGbYs - (3GdehShj(B, (3VjGA eLjOs ((3GdLRGFQs (3cfhR GdMceIs, 2015)
(3GdHfc GdeQcRj h GdSjGSGJ GdeGdjI h GdfbOjI , GSJbdGdjI GdHfc GdeQcRj , GdHfhc GdeQcRjI LRAG ef GdeTcdI h CjVG LRAG ef GdMd , SjGSI CSJgOGa GdJNVe , SYQ GdUQa h GdSjGSI GdfbOjI , Jehjd GdJLGQI GdNGQLjI(B.s
Keywords: (3GdHfhc GdeQcRjIs